Pendampingan 'Scale-Up' UMK Kuliner Tradisional sebagai Upaya Peningkatan Ekonomi Masyarakat Desa Terusan - Mar Atun Saadah; Anggun Suri; Mohd. Norma Sampoerno; Mawarnis Hapsari Utomo (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Terusan Village is famous for its agricultural and fishery potential, processed superior products in the form of processed dodol, banana and cassava chips, crackers and fish crackers. However, the production of processed agricultural and fishery products is still marketed in a limited manner by relying on relations. This marketing limitation is certainly caused by other systemic problems in the form of the absence of a Business Identification Number (NIB), Household Industry Food Permit (PIRT) and Halal Certificate (SH). The author identifies solutions to these problems with the concept of 'Scale Up' or class improvement. The implementation of activities is carried out by involving community participation as the main actors in changing both attitudes and knowledge. Mentoring activities begin with basic entrepreneurship training in the form of an introduction to business legality and its urgency. Furthermore, the team conducted a workshop on the selection of packaging design and digital product marketing which is ultimately expected to support the improvement of packaging quality and marketing reach through digital marketing. This class improvement has an impact on product quality and marketing reach, this has an impact on increasing the economic level of village communities through increased sales.